Characterizing the metabolic perturbations induced by activity-based anorexia in the C57Bl/6 mouse using 1H NMR spectroscopy. Issue 8 (August 2020) - Breton, Jonathan; Giallourou, Natasa; Nobis, Severine; Morin, Aline; Achamrah, Najate; Goichon, Alexis; Belmonte, Liliana; Dechelotte, Pierre; Rego, Jean-Luc do; Coëffier, Moïse; Swann, Jonathan
Summary: Background & aims: Anorexia nervosa (AN) is a severe psychological and potentially life-threatening eating disorder. The activity-based anorexia (ABA) mouse model is commonly used to investigate physiological abnormalities associated with this disorder. Characterizing the holistic biochemical alterations induced by anorexia is essential to understanding AN pathophysiology as well as to define biomarkers for prognosis. Methods: To unravel the adaptive biochemical mechanisms occurring in this model in response to self-starvation, the urinary, plasma and fecal metabolic phenotypes of mice under different experimental conditions were compared. This included control mice with and without physical activity (CT and CTPA mice), a group with limited food access (LFA), and a group with both limited food access and physical activity (ABA). Using 1 H nuclear magnetic resonance (NMR) spectroscopy, several biochemical perturbations were observed. Results: Physical activity altered the abundance of 14 fecal metabolites, including those involved in gut microbial metabolism and proteolysis. Food restriction disrupted a wide range of metabolic pathways including gut microbial metabolism, proteolysis and fatty acid breakdown (24 urinary and 6 plasma metabolites). The combined impact of food restriction and physical activity resulted in the same pattern of metabolic disruption (24 urine, 6 plasma). Conclusions: This work defined the metabolic signatures of ABA mice and provides novel insights into biological adaptations of mice in response to both food restriction and physical activity. These results should be further confirmed in AN patients.